Faktor Yang Berhubungan Dengan Perilaku Pengendalian Tekanan Darah Pada Penderita Hipertensi Di Puskesmas Harapan Raya Kota Pekanbaru Tahun 2016: Faktor Yang Berhubungan Dengan Perilaku Pengendalian Tekanan Darah Pada Penderita Hipertensi Di Puskesmas Harapan Raya Kota Pekanbaru Tahun 2016 - Riri Maharani; Dary Putri Syafrandi (Jurnal Kesehatan Komunitas, 2017)
Hypertension is a major cause of stroke that cause a high mortality. This situation happens in the world, both in developed countries and developing countries. Data obtained from Harapan Raya Community Health Center showed increasing cases of hypertension since 2014 (4879 cases) until 2015 (5208 cases). The aim of this study was to obtain the related factors to blood pressure controlling behavior in the hypertension patients in the Harapan Raya Community Health Center, Pekanbaru. This quantitative analytical research used a cross sectional study. Population was hypertension patients between May 12 and June 12 2016 at Harapan Raya Community Health Center. Subjects were 152 hypertension patients who visited community health center. The sampling technique was accidental sampling. The instrument used questionnaires and computerized data processing. The statistical analysis used univariate and bivariate with Chi-square test. The results showed that related factors to blood pressure controlling behavior in the hypertension patients were knowledge (p-value =0.022, POR = 2.263; 95%CI: 1,171-4,372 ), attitude (p-value = 0.025, POR = 2.249; 95%CI: 1,155-4,564), diet (p-value = 0,027, POR = 2.296; 95%CI: 1,155-4,564), sport (p-value <0,005,POR = 3.850; 95%CI: 1,867-7,940), family support (p-value = 0.032 , POR = 2.157; 95%CI: 1,118-4,161), and the role of health workers (p-value = 0.005,POR = 2.798; 95%CI: 1,407-5,561). We recommend to Harapan Raya Community Health Center to improve intensive counseling and prevention about risk factors that related to hypertension besides spreading brochures explaining about hypertension and its impacts.